MMPP promotes adipogenesis and glucose uptake via binding to the PPARγ ligand binding domain in 3T3-L1 MBX cells - Kim, Na-Yeon; Lim, Chae-Min; Park, Hyo-Min; Kim, Jinju; Pham, Thu-Huyen; Yang, Young; Lee, Hee Pom; Hong, Jin Tae; Yoon, Do-Young (Frontiers in Pharmacology, 2022)
Peroxisome proliferator-activated receptor-gamma (PPARγ) is a transcription factor involved in adipogenesis, and its transcriptional activity depends on its ligands. Thiazolidinediones (TZDs), well-known PPARγ agonists, are drugs that improve insulin resistance in type 2 diabetes. However, TZDs are associated with severe adverse effects. As current therapies are not well designed, novel PPARγ agonists have been investigated in adipocytes. (E)-2-methoxy-4-(3-(4-methoxyphenyl) prop-1-en-1-yl) phenol (MMPP) is known to have anti-arthritic, anti-inflammatory, and anti-cancer effects. In this study, we demonstrated the adipogenic effects of MMPP on the regulation of PPARγ transcriptional activity during adipocyte differentiation in vitro. MMPP treatment increased PPARγ transcriptional activity, and molecular docking studies revealed that MMPP binds directly to the PPARγ ligand-binding domain. MMPP and rosiglitazone showed similar binding affinities to the PPARγ. MMPP significantly promoted lipid accumulation in adipocyte cells and increased the expression of C/EBPβ and the levels of p-AKT, p-GSK3, and p-AMPKα at an early stage. MMPP enhanced the expression of adipogenic markers such as PPARγ, C/EBPα, FAS, ACC, GLUT4, FABP4 and adiponectin in the late stage. MMPP also improved insulin sensitivity by increasing glucose uptake. Thus, MMPP, as a PPARγ agonist, may be a potential drug for type 2 diabetes and metabolic disorders, which may help increase adipogenesis and insulin sensitivity.